Investigation of active reactive power based on synchronous reference frame for the frequency control of islanded microgrid: under different line impedance ratio - Nicholaus Moyo; Baraka Kichonge; Thomas Kivevele (Discover Applied Sciences)
Abstract The low inertia of distributed renewable energy sources, along with the increasing complexity and use of nonlinear and unbalanced loads in modern distribution systems, has led to power quality (PQ) issues, including harmonics, voltage imbalance, and power factor deterioration. The presence of harmonics and unbalanced voltage distort the frequency and voltage waveforms, leading to microgrid frequency instability that negatively affects microgrid control, protection systems, as well as operational performance and life span of sensitive electrical equipment. This study proposes design of an Active Reactive Power controller based on a Synchronous Reference Frame using an Adaptive Network Fuzzy Inference System (ANFIS) control technique for secondary frequency control. ANFIS leverages the strengths of both fuzzy logic and neural networks. This integration allows ANFIS controllers to capture and utilize both quantitative and qualitative information for control decision-making, enhancing their performance in complex microgrid environments compared to conventional controllers. The primary goals of the proposed method are to regulate system frequency, minimize the total harmonic distortion (THD) and enhance the power factor (PF). The effectiveness of the proposed method is evaluated through three testing scenarios of distribution line impedance involving four different load conditions, with result compared to conventional droop controller. The analysis reveals that the THD for case studies 0.3%,2.76%, 2.08. 2.25%, 0.27%, 2.41%, 1.94%, 2.15%, 0.15%, 2.25%, 1.85% and 1.71%, significantly lower than conventional droop controller. Additionally, the PF is nearly unity, with average of 20% improvement in frequency response settling time and 68.6% reduction in maximum frequency deviation.